Perbandingan Pertumbuhan Mucuna bracteata Pada Berbagai Macam Pupuk dan Komposisi Media Tanam - Edo CHriziayanto Putra Anggara Nababan; Pauliz Budi Hastuti; Wiwin Dyah Ully Parwati (Universitas Merdeka Madiun, 2023)
The research was carried out at the Sungai Bungur Estate Plantation (SBGE), PT. Prisma Cipta Mandiri, South Sumatra Region 2, PSM 2 located in Cempaka Sari Village, East Kikim, Lahat Regency, South Sumatra. This research was conducted from March 2023 - April 2023. The research method used to analyze the results of this research was a 2-factor Completely Randomized Design (CRD). The first factor is the type of fertilizer with 3 levels: urea 5 g/polybag, rock phosphate (RP) 50 g/polybag, NPKMg 5 g/polybag. The second factor is the composition of the planting medium with 3 levels: top soil, top soil: 1:1 manure, and top soil: 2:1 manure. Observational data Ade analyzed Alt variance at the 5% level. To find out the differences betwween treatments the Duncan’s Multiple Range Test bas continued St 5% level. The parameters observed were the increase in seedling height, number of leaves, stem diameter, root length, root volume, shoot fresh weight, shoot dry weight, root fresh weight, root dry weight. The results of the analysis show that the combination of applying NPKMg fertilizer with the composition of top soil planting media: manure 2:1 shows that there is a real interaction on the parameters of shoot dry weight, root fresh weight and root dry weight.